2008
DOI: 10.1371/journal.pcbi.1000216
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Modes of Regulation by Chromatin Encoded through Nucleosome Positioning Signals

Abstract: The detailed positions of nucleosomes profoundly impact gene regulation and are partly encoded by the genomic DNA sequence. However, less is known about the functional consequences of this encoding. Here, we address this question using a genome-wide map of ∼380,000 yeast nucleosomes that we sequenced in their entirety. Utilizing the high resolution of our map, we refine our understanding of how nucleosome organizations are encoded by the DNA sequence and demonstrate that the genomic sequence is highly predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
589
6
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 411 publications
(665 citation statements)
references
References 73 publications
(218 reference statements)
51
589
6
10
Order By: Relevance
“…In agreement with this inference, previous studies mapping genome-wide nucleosome positions at steady state have discovered a strong enrichment of predicted transcription factor binding sites in NDRs (Yuan et al, 2005;Lee et al, 2007;Morse, 2007;Field et al, 2008). Extending these studies, we found that gene promoters with an accessible transcription factor binding motif are significantly more likely to be regulated like known targets of that transcription factor than promoters where the motif is occluded by a nucleosome.…”
Section: Preset Promoterssupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with this inference, previous studies mapping genome-wide nucleosome positions at steady state have discovered a strong enrichment of predicted transcription factor binding sites in NDRs (Yuan et al, 2005;Lee et al, 2007;Morse, 2007;Field et al, 2008). Extending these studies, we found that gene promoters with an accessible transcription factor binding motif are significantly more likely to be regulated like known targets of that transcription factor than promoters where the motif is occluded by a nucleosome.…”
Section: Preset Promoterssupporting
confidence: 89%
“…These preset promoters tend to be underrepresented for TATA boxes and tend to have a strong nucleosome-depleted region at a stereotypical position relative to the transcriptional start site, a promoter architecture that has been termed "type II" (Field et al, 2008). Previous work has characterized TATA-less promoters as enriched in constitutively expressed housekeeping genes (Basehoar et al, 2004), but the work reported here clearly demonstrates that individual TATA-less preset promoters are capable of dramatic gene expression changes.…”
Section: Preset Promotersmentioning
confidence: 67%
“…We employed a statistical model inspired by that of Segal et al (13), Field et al (16), and Kaplan et al (18). However, whereas their models are trained on experimental data, we employed this type of model to create a computationally inexpensive approximation to the theoretical nucleosome model recently published in Eslami-Mossallam et al (4).…”
Section: Modelmentioning
confidence: 99%
“…Around the TSS of Saccharomyces cerevisiae (baker's yeast), nucleosomes have been found to be depleted on average, both in vitro and in vivo (12)(13)(14)(15)(16)(17)(18). The persistence of this depletion in vitro, in the absence of active remodeling, identifies the sequence preferences of nucleosomes as the dominant cause.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation